The voice of the florist. A message about we-ness awareness - Michopoulou, Joanna (Murmurations: Journal of Transformative Systemic Practice, 2022)
As a systemic therapist, I have found Karen Barad’s physics-philosophy useful when trying to comprehend understandings of my responses from within the ongoing stream of my interactions with clients. In this writing, I attempt to share my understanding of Barad’s ideas of “performativity” and “phenomena” through the making of a bouquet in the flower shop down the road. The essay unfolds around a brief dialogue with the florist, and around my inner dialogue and reflections in relation to his question to me: “Did they like what we made?”. I am focusing on the entangled nature of doing, knowing and being, and the radical aliveness of relational responsivity in our encounters with people. Drawing upon the relational wisdom of everyday spontaneous living with others to enrich professional practice, I am showing that ethical concerns are not supplemental to practice but an integral part of it (Barad, 2007, p. 37). The choice of episode is random but its spontaneous nature fits with the notion of a “phenomenon”. It is a simple, brief, mostly non-verbal occasion, allowing for a real-ist performance improvisation of complementary intra-acting agencies, emerging from within their intra-action, without the need for evaluating and measuring separate individual agencies and actions. According to Barad (2007, p. 37), “realism is not about representations of an independent reality but about the real consequences, interventions, creative possibilities, and responsibilities of intra-acting within and as part of the world.” In my effort to show that “values are integral to the nature of knowing and being” (Barad, 2007, p. 37), I have avoided the urge for reflections based on hypothesising about what might be indicating what or theorising about what might mean what in this essay. Instead, I let entangled and overlapping knowledges from various areas and times of my life and practice interact, and through a kind of “diffractive” writing, I am in dialogue with the reader; with myself backdated to the day when I went to the flower shop to buy the bouquet; with myself as a therapist and a researcher; with Barad through the use of a number of quotations from her work; and with a number of novel and fictional heroes who, although unrelated to the theme of this writing, come to my mind as I relive the episode I am writing. Περίληψη (Greek) Σαν συστημική θεραπεύτρια, έχω βρει τις φιλοσοφικές ιδέες της Karen Barad χρήσιμες στις προσπάθειες μου να καταλάβω διαφορετικές κατανοήσεις των τρόπων με τους οποίους ανταποκρίνομαι στους πελάτες μου μέσα στη ροή της διάδρασης μας. Σε αυτό το άρθρο επιχειρώ να μοιραστώ το πως αντιλαμβάνομαι τις έννοιες της «επιτελεστικότητας» και του «φαινομένου», που χρησιμοποιεί η Barad, μέσα από τη δημιουργία μιας ανθοδέσμης στο ανθοπωλείο της γειτονιάς μου. Το κείμενο ξεδιπλώνεται γύρω από ένα σύντομο διάλογο με τον ανθοπώλη, και την ερώτηση που μου κάνει: «τους άρεσε αυτό που φτιάξαμε;». Επικεντρώνομαι στην διεμπλεκόμενη φύση της πράξης, της γνώσης και της ύπαρξης και την βαθιά ζωντανότητα της σχεσιακής απαντητικότητας στις συναντήσεις μας με τους άλλους.